2008
DOI: 10.3846/1648-4142.2008.23.279-286
|View full text |Cite
|
Sign up to set email alerts
|

Governance and Institutions of Transportation Investments in U.S. Mega‐regions

Abstract: From a planning perspective, a mega‐region can be defined as an extended network of metropolitan centers and their surrounding areas, crossing county and state lines, linked by integrated labor markets, land use systems and transportation and communication infrastructure. From a governance perspective, delimiting the jurisdictional borders of a mega‐region is rather challenging due to the overlap of hierarchy of governance systems. It has been suggested that the effective management of existing transportation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…They admit that while the investment in HSR may have concerns such as imbalanced development within a megaregion, planners and decision makers have an important role in shaping it in the most beneficial way (Melibaeva et al, 2011). Vega and Penne (2008) surveyed multiple emerging institutional arrangements to deal with regional and megaregion planning and development in transportation infrastructure and found that investment in megaregion-level transportation infrastructure can be beneficial, while noting that issues such as delineating megaregion boundaries and coordinating regional frameworks of governance are challenges. The complexity of the potential impacts of investing in HSR reveals the important role that planners and decision makers can play in shaping the economic growth and development at a large geographic scale.…”
Section: Enhancing Economic Competitiveness Through Megaregion Transpmentioning
confidence: 97%
“…They admit that while the investment in HSR may have concerns such as imbalanced development within a megaregion, planners and decision makers have an important role in shaping it in the most beneficial way (Melibaeva et al, 2011). Vega and Penne (2008) surveyed multiple emerging institutional arrangements to deal with regional and megaregion planning and development in transportation infrastructure and found that investment in megaregion-level transportation infrastructure can be beneficial, while noting that issues such as delineating megaregion boundaries and coordinating regional frameworks of governance are challenges. The complexity of the potential impacts of investing in HSR reveals the important role that planners and decision makers can play in shaping the economic growth and development at a large geographic scale.…”
Section: Enhancing Economic Competitiveness Through Megaregion Transpmentioning
confidence: 97%
“…Generally speaking, natural condition, location advantage, self-organization and endogenous growth, spillover effect as well as industrial concentrations are important factors affecting UA development (Benguigui, 1992;Arthur, 1994;Krugman, 1996;Fujita et al, 1997;Baruch, 1997;Duranton et al, 2000;Berliant, 2006). Besides, there is a series of guidelines for urbanization, and the government coordination mechanism is built to enhance intergovernmental collaboration (Vega et al, 2008;Hershberg, 1996;Frisken, 1991). There is hardly any special strategies and organization to managing development and spatial structure of UAs except some mandatory behaviors existing in Japan and Korea.…”
Section: Comparison With Development Of Foreign Urban Agglomerationsmentioning
confidence: 99%
“…Transport is of vital importance for the society because it contributes to economic development (Sivilevicius 2011;Maciulis et al 2009;Ginevicius, Podvezko 2009;Zvirblis, Zinkeviciùté 2008;Li et al 2009;Vega, Penne 2008;Prentkovskis et al 2009b;Vasilis Vasiliauskas et al 2010;Jakimavicius, Burinskiené 2009;Jauneikaité, Carreno 2009;Jovic, Depolo 2011); however, in addition to its positive impact on the economy, transport causes an adverse effect on the society and environment. A considerable harm is caused by traffic accidents when humans perish and are injured, vehicles and road constructions are damaged, the environment is polluted by spilled fuels, oils and transported materials (Baltrenas, Kazlauskiené 2009;Baltrenas et al 2008;Baltrenas, Puzinas 2009;Peceliünas, Prentkovskis 2006;Vaisis, Januáevicius 2009;Prentkovskis et al 2009aPrentkovskis et al , 2010aPrentkovskis et al , 2010bSapragonas, Darguzis 2011;Rukuiza, Eidukynas 2009;Cygas et al 2009;Leipus et al 2010;Pellegrino 2009;Antov et al 2009;Cerniauskas et al 2010;Vitkùnas, Meidute 2011;Jagniatinskis et al 2011).…”
Section: Introductionmentioning
confidence: 99%